PENGARUH MEDIA PEMBELAJARAN CAI ( Computer Assisted Instruction ) TERHADAP HASIL BELAJAR SISWA SMP ISLAM CIBATUTIGA CARIU-BOGOR - Olis (JURNAL KADESI, 2023)
Good learning media is learning media that can increase student motivation. The use of media has the aim of providing motivation to students. In addition, the media must also stimulate students to remember what they have learned apart from providing new learning stimuli. Good media will also activate students in providing responses, feedback and also encourage students to always pay attention to the material being conveyed by the teacher with the help of the media, there will be an interactive learning, fun learning.